BUDDHIST EMOTIONAL INTELLIGENCE : INTEGRATING DHARMA PRINCIPLES INTO A HAPPY WORKPLACE IN BANI WORLD ERA - Singsorn, Natataporn; Sukpom, Thitiwas; Nilkote, Reongwit; Saisena, Natthapat; Papan , Nattakorn (Journal of MCU Nakhondhat, 2024)
This article aims to present the Buddhist way of emotional intelligence by analyzing the integration of Dharma principles into a happy organization in the changing era. Because it is a skill that human resources in a changing world need. Happiness is an important emotional intelligence at work, it is considered a very important factor for the management of the organization, which directly affects both the individual level in order to create motivation to work more efficiently and affects the organization to make the organization a place of happiness. Creating a culture of happiness in an organization will take time to change attitudes that have been accumulated for a long time. It requires patience, commitment to problem solving and effort to create happiness in the organization. Buddhism is believed to be a religion of education and development of individual potential. Achieving Buddhist goals aims to develop a comfortable mind in the midst of various situations. The approach to integrating emotional intelligence according to the Buddhist approach includes: 1) The development of emotional intelligence according to the principles of mindfulness are Kãyãnupassanã, Vedanãnupassanã, Cittãnupassanã and Dhammãnupassanã, and 2) The development of emotional intelligence according to the Yonisomanasikãra principle, consisting of discriminating between components, blame and exit thinking, investigative thinking, and interrelated thinking with goal principles. Problem - solving thinking, simple cognitive thinking. Think of genuine values, artificial values. Think morally, think in the present moment, and think in isolation.